2022
DOI: 10.1021/acsami.2c08370
|View full text |Cite
|
Sign up to set email alerts
|

γ-Ester-Functionalized 1,1-Dicyanomethylene-3-indanone End-Capped Nonfullerene Acceptors for High-Performance, Annealing-Free Organic Solar Cells

Abstract: Modifying the end-capping groups in nonfullerene acceptors (NFAs) is an effective strategy for modulating their properties and that of the entire NFAs. This study reports the synthesis of a novel γ-ester-functionalized IC end-capping group (IC-γe) and its incorporation into the benzothiadiazole-fused central core, yielding isomer-free IC-γe end-capped NFAs, such as Y-IC-γe, Y-FIC-γe, and Y-ClIC-γe. The resultant NFAs exhibited similar absorption profiles but upshifted the lowest unoccupied molecular orbital en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(14 citation statements)
references
References 73 publications
0
14
0
Order By: Relevance
“…56,57 Accordingly, we expected that different T g values in the FY NFAs could affect the corresponding devices' thermal stability and their active layers' morphological properties under applied continuous thermal stress. To precisely investigate the effect of FY NFA T g on the thermal stability of OSC devices, the unencapsulated devices, less the electron transport layer and top electrode, were fabricated and stored under an N 2 atmosphere with a continuous thermal stress of 85 °C for 0−360 h. 11 After thermal treatment for the specified amount of time, the electron transport layer (PDINO) and top electrode were deposited on each active layer, and the corresponding OSC devices' photovoltaic properties were measured (Figure 7). The 4FY-based OSC exhibited 88.4% PCE retention after 360 h, whereas the 2FY-based OSC retained only 79.0% PCE after 360 h. This indicated that 4FY exhibited better thermal stability in OSC devices than 2FY.…”
Section: Photovoltaic Performance and Charge Carrier Dynamicsmentioning
confidence: 99%
See 2 more Smart Citations
“…56,57 Accordingly, we expected that different T g values in the FY NFAs could affect the corresponding devices' thermal stability and their active layers' morphological properties under applied continuous thermal stress. To precisely investigate the effect of FY NFA T g on the thermal stability of OSC devices, the unencapsulated devices, less the electron transport layer and top electrode, were fabricated and stored under an N 2 atmosphere with a continuous thermal stress of 85 °C for 0−360 h. 11 After thermal treatment for the specified amount of time, the electron transport layer (PDINO) and top electrode were deposited on each active layer, and the corresponding OSC devices' photovoltaic properties were measured (Figure 7). The 4FY-based OSC exhibited 88.4% PCE retention after 360 h, whereas the 2FY-based OSC retained only 79.0% PCE after 360 h. This indicated that 4FY exhibited better thermal stability in OSC devices than 2FY.…”
Section: Photovoltaic Performance and Charge Carrier Dynamicsmentioning
confidence: 99%
“…9 Since this pioneering work, considerable progress has been made in the design and synthesis of molecular structures toward superior Y-series NFAs. 4,10,11 Side-chain engineering is one of the most efficient strategies for fine-tuning NFAs. 12−141516 Y-series NFAs possess two sets of alkyl side chains, with the inner pair located on the pyrrole rings and the outer pair flanking at the 2-positions of the thienothiophene moieties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several attempts have been made for p-framework variation, including changing the heteroatom of the core DA ′ D structure, modulating the p-extension of fused rings, and attaching different end-capping units. [14][15][16] This modulation simultaneously inuences the intrinsic molecular electronic properties (such as the absorption spectrum and energy level) and intermolecular interactions. Another efficient approach for advances in Y-series NFAs is alkyl side-chain alternation, which primarily affects intermolecular interactions.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of the NFAs, A-DA 0 D-A-type ‡ molecular frameworks are one of the most popular design strategies following the development of the Y6 acceptor. [4][5][6] For polymer donors, D-A-type copolymer designs using weak electron donor and strong/medium electron acceptor units have been adopted for high-performing wide-bandgap polymers, resulting in the appearance of representative widebandgap donors PM6 and D18. [7][8][9] For the design and combination of wide-bandgap polymer donors and NFAs, the following attributes should be considered: (i) absorption complementarity, (ii) energy level matching, (iii) suitable phase separation, and (iv) molecular orientation/crystallinity tendency between the widebandgap polymer donor and NFA.…”
mentioning
confidence: 99%